New ways to learn science with enjoyment: robotics as a challenge - Ribeiro, A. Fernando (2009)
It is well known that during their learning process youngsters prefer and enjoy exciting challenges, so that they don’t get bored in school. Many of those challenges are blossoming all around the world in an annual basis, and they stimulate students because they create new objectives, they allow creativity, discovering new and unique solutions and allow comparison of the work carried out by other teams. The robotics interest has been growing quickly and many schools are adopting this knowledge area due to its multidisciplinary, for being stimulating, for allowing students creativity, for being so practical and hands-on, and it technologically sounds good. Many challenges have being created in the last few years, both pedagogical and competitive, and requiring different levels of know-how. This paper describes the most important robotics challenges in terms of it main objectives and rules, the age target, its geographical localization, its average budget and the first steps to be taken for new teams. After reading this paper teachers will be able to decide which robotic challenge is more suitable for his team.